Teachers Efforts in Evaluating Islamic Religious Education Learning Using Discussion Learning Methods - Rohmah, Wuwun Dwi Fathur; Mislikhah, Siti; Sutomo, Sutomo (Sekolah Tinggi Ilmu Tarbiyah (STIT) Muhammadiyah Bangil in collaboration with Letiges & Association of Muslim Community in ASEAN (AMCA), 2024)
This research evaluates Islamic education learning carried out by teachers at Public Middle School 1 Panji. This research method uses a qualitative approach, and the type of research used is field research. Selection of Research Subjects This research method uses a qualitative approach, and the kind of research used is field research. Teachers and students at Public Middle School 1 Panji proposed the choice of research subjects. The data collection techniques used in this research are observation, interview and documentation. The data analysis used by researchers is data analysis from Miles and Huberman's ideas, namely data condensation, data presentation, and concluding/verification. Islamic education learning requires a process to help students learn the Islamic religion. Evaluations carried out by teachers, both assessments of the learning process and evaluations of learning outcomes, are carried out to maximize students' intelligence in terms of knowledge, enjoyment of life, and ability to interact physically and socially. In the community environment. Islamic education learning must be pursued through good planning to influence students' choices, decisions and life developments. The evaluation results carried out by Islamic education teachers are effective and can increase students' active learning and thinking during the learning process and its application in everyday